Kepemimpinan Kepala Tata Usaha dalam Mengembangkan Pengelolaan Arsip Dinas Pendidikan Kabupaten Gresik - Aisyah Anis Maisyaroh (JURNAL MAPPESONA, 2024)
This research aims to examine the leadership of the administrative head in managing archives at the Gresik Regency Education Office. The main problem faced is a lack of orderly records management due to the lack of special storage areas, limited human resources and networks in electronic systems, as well as the absence of special personnel to handle records. The method used is qualitative with a descriptive approach, with data obtained through interviews, observation and documentation. The research results show that the head of administration at the Gresik Education Service is in charge of planning, implementing, providing and reporting general administrative tasks as well as managing office equipment, including the provision, maintenance of facilities, personnel administration and archive management. Archives management includes the process of creating, storing and retrieving archives, both manually and digitally. Even though there have been digitalization efforts, improving archives management is still needed, especially in providing facilities such as archive houses or storage areas in each field, system development, as well as increasing human resources through training or socialization about archive management.